Space-Oriented Decision-Making and Responsibility Competence – A Critical View - Köck, Helmuth (Journal of Geography Education, 2011)
Concluding Robinsohn (1967), who thought of education as configuration to behaviour of the world and the aim of education as aim of behaviour, the author initiated spaceoriented behavioural competence as a headline goal of geography in school. Although the definition found wide acceptance, the definition of space-oriented decision-making and responsibility was proposed to be an alternative (Hasse 1980, 1986; Thöneböhn 1986, 1995). In the “fundamentals and references …” (2003) as well as “educational standards …” (2008) the definition of space-oriented decision-making and responsibility has been declared as headline goal of geography lessons. Concluding previous critical definitions of space-oriented behaviour and space-oriented decision-making and responsibility (primarily 1989, 1997), this article will contemplate the three components of space-oriented decision-making and responsibility competence, namely space, decision-making and responsibility and competence on a critical basis. The review will clarify if all components together subsume the goals of geography lessons. This is expected from a headline goal. Precisely: Is the construction of decision-making adequate to subsume the individual components of geography lessons? Is competence what geography lessons aim for? And finally, to which space-oriented construct does decision-making allude to? The result of this article should lead to an analysis of a conceptual construct, in which requirements of a main aim are fulfilled and conducted to geographical teaching and studying.